If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 7) + -11 = 54 Reorder the terms: 5(7 + 3x) + -11 = 54 (7 * 5 + 3x * 5) + -11 = 54 (35 + 15x) + -11 = 54 Reorder the terms: 35 + -11 + 15x = 54 Combine like terms: 35 + -11 = 24 24 + 15x = 54 Solving 24 + 15x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 15x = 54 + -24 Combine like terms: 24 + -24 = 0 0 + 15x = 54 + -24 15x = 54 + -24 Combine like terms: 54 + -24 = 30 15x = 30 Divide each side by '15'. x = 2 Simplifying x = 2
| (-8)(-2)= | | 5+4p-8p=-19 | | 14y^3-4x^2+2-6y^3-2x^2= | | x^2+10x+-4=0 | | -9x-8=1x+16 | | 2x=(7x-y) | | 1+2n+6n=-7 | | 7x+96=-5x | | 368317*8= | | 20/x=4/9 | | 415441*9= | | -23=6-5n-4 | | 415441*10= | | 4(x-7)-2=2(x-3) | | 5k-2k=-21 | | 368317*10= | | 10x-8=9x-5 | | 458000*8= | | -16=-3p+p | | 449000*8= | | 3n=4n-4 | | 8n+3n=-22 | | 2x+26=44 | | 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h |